Revolutionary passions - Bozarslan, Hamit, author.
1 online resource (viii, 202 pages)
Keywords: "Europe has been the chief arena of revolutionary passions since the end of the eighteenth century. During this same period, and right up to the beginning of the twenty-first century, the non-European world, too, has resonated with coup attempts and revolutionary turmoil. How does one begin to understand these revolutionary passions? To what extent are they influenced by European matrices? Have these revolutions also themselves resulted in 'exportable models'? Three French writers look at three continents--Latin America, the Middle East and India and interrogate the revolution, with reference to and dialogue with the definitive work of Francois Furet, who wrote The Passing of an Illusion: The Idea of Communism in the Twentieth Century. Interestingly, the original French book Passions revolutionnaires was written in 1995, just after the fall of the Berlin wall. Whether nationalist, religious, proletarian, international, anti-colonial or simply liberty and equality, whether violent or fought passively, the Revolution as a concept and a fact, whether past, present or future, remains a critical reference point for our societies. "--Provided by publisher.